2015
DOI: 10.1007/s40279-015-0314-y
|View full text |Cite
|
Sign up to set email alerts
|

Weightlifting Pulling Derivatives: Rationale for Implementation and Application

Abstract: This review article examines previous weightlifting literature and provides a rationale for the use of weightlifting pulling derivatives that eliminate the catch phase for athletes who are not competitive weightlifters. Practitioners should emphasize the completion of the triple extension movement during the second pull phase that is characteristic of weightlifting movements as this is likely to have the greatest transference to athletic performance that is dependent on hip, knee, and ankle extension. The clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
115
0
17

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 108 publications
(151 citation statements)
references
References 147 publications
(298 reference statements)
1
115
0
17
Order By: Relevance
“…However, the speed at which the movement is performed, and therefore the load, must be considered. The jump shrug (97) and hang high pull (96) are 2 of the most ballistic weightlifting derivatives that may be highlighted in a speed-strength training phase (95). Similar to the strength-speed phase, a combination of heavy and light loaded derivatives should be implemented to optimize RFD and power adaptations.…”
Section: Speed-strengthmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the speed at which the movement is performed, and therefore the load, must be considered. The jump shrug (97) and hang high pull (96) are 2 of the most ballistic weightlifting derivatives that may be highlighted in a speed-strength training phase (95). Similar to the strength-speed phase, a combination of heavy and light loaded derivatives should be implemented to optimize RFD and power adaptations.…”
Section: Speed-strengthmentioning
confidence: 99%
“…This is likely due to the similarities between the rate and pattern of hip, knee, and ankle triple extension that occur during weightlifting movements and sport skills such as vertical jumping (7,8,36,52,53,81), sprinting (52), and change of direction tasks (52), as well as the ability to provide an overload stimulus (95). In addition, it has been suggested that weightlifting movements may be used to train the muscular strength that is required during impact tasks, such as jump landing (68).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…(Castillo, Valverde, Morales, P茅rez-Guerra, De Le贸n, and Garc铆a-Manso, 2012;Comfort, Fletcher and McMahon, 2012a;Cormie, McGuigan and Newton, 2011;Kawamori and Haff, 2004;Suchomel, Comfort and Stone, 2015;Suchomel, Wright, Kernozek and Kline, 2014). To maximize the power output during any exercise there must be an optimum relationship between force and velocity.…”
Section: Introductionmentioning
confidence: 99%